2019
DOI: 10.1002/pon.5167
|View full text |Cite
|
Sign up to set email alerts
|

Psychological correlates of sleep quality in lung cancer patients under chemotherapy: A single‐center cross‐sectional study

Abstract: Objectives: Disturbed sleep is a common complaint of lung cancer patients undergoing active oncologic treatment. We aimed to clarify the extent to which psychological symptoms, coping strategies, and social support interfere with sleep quality and whether they mediate the relationship between sleep quality and fatigue or functional capacity in a sample of chemotherapy treated lung cancer patients.Methods: Lung cancer patients attending an oncology unit for scheduled chemotherapy cycles completed questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Most data regarding sleep disorders are gathered from patients who were diagnosed lung cancer, were undergoing chemotherapy, or were long-survivors. [14][15][16][17] Studies have reported a high psychological burden affecting quality of life. 18 Of interest, sleep quality was found to be prognostic factor for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Most data regarding sleep disorders are gathered from patients who were diagnosed lung cancer, were undergoing chemotherapy, or were long-survivors. [14][15][16][17] Studies have reported a high psychological burden affecting quality of life. 18 Of interest, sleep quality was found to be prognostic factor for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Distress and disturbed sleep are two common persistent symptoms [37,38], and higher psychological distress can predict sleep disturbances [39,40]. Our results revealed that although the peak scores for sleep and psychological symptoms were not particularly high, distress and disturbed sleep persisted before surgery to 90 days after surgery; at 90 days after surgery, approximately 50.58% of patients still reported sleep disturbances.…”
Section: Persistence Of Disturbed Sleep and Distressmentioning
confidence: 65%
“…Although graded nursing did not exhibit any significant impact on the incidence of adverse events, it still significantly improved the QoL of NSCLC patients in our study. There are a number of previously published studies exploring efficient measurements to improve the QoL of NSCLC patients (19)(20)(21)(22)(23)(24)(25)(26)(27). The co-administration of conventional chemotherapeutic agents and novel drugs provides an option.…”
Section: Discussionmentioning
confidence: 99%